(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Nodal segments from naturally grown Eclipta alba (L.) Hassk.were used as explants for organogenesis. Multiple shoots were obtained from the explants cultured on MS medium supplemented with various concentrations of BAP and Kn alone or in combination with NAA and IAA. Maximum number of multiple shoots (18.40±0.67) were induced on MS medium supplemented with 1.0 mg/l BAP and 0.1mg/NAA. In vitro raised shoots were cultured onto half and full strength MS medium supplemented with different concentration of IBA, IAA and NAA. The best root induction medium was found to be half strength MS containing 0.1 mg/l IBA where 96% shoots rooted. Regenerated plantlets grew normally without showing any morphological variation and flowered after 45 days of transplantation. Jahangirnagar University J. Biol. Sci. 4(1): 61-69, 2015 (June)